A review on the mechanical methods for evaluating coating adhesion - Lam, Yee Cheong (2016)
Coatings have been applied widely in aerospace, biomedical, electronic, and many other industries. The performance of a coating is dictated by the adhesion between the coating and the underlying substrate. Thus, the evaluation of coating adhesion is critical for the assessment of the quality of a coating and its fitness for service. However, this evaluation is not straightforward, and various mechanical and non-mechanical evaluation methods have been developed. This paper presents a comprehensive review of the currently most widely employed mechanical methods. The interface fracture mechanics that provides the fundamental knowledge for conducting adhesion assessment and analysis is briefly introduced. Detailed discussions are presented on various sandwich specimen-based and bimaterial specimen-based testing methods, with emphasis on the principles, merits, limitations, typical applications, and recent improvements of each method.